Estudo clínico do biofilme de próteses totais implantossuportadas - Oliveira, Iana Sá de (2019)
The implant-supported prosthesis protocol has demonstrated a great improvement in the masticatory performance of total edentulous patients, since they have excellent retention and stability. The biofilm control, however, is hampered by the design of the prosthesis, which can cause peri-implantitis, mucositis, prosthetic stomatitis, tissue hyperplasia, aesthetic problems, among others. The aim of this clinical research was to quantify the biofilm of the gingival face of mandibular implants and to identify bacteria and fungi in the present biofilm. Twenty total edentulous patients were evaluated using implant-supported prothesis of protocol type in acrylic resin in the lower arch. The inclusion criteria were: adults, any genus, totally edentulous in the mandibular arch, with good general health status, protocol type prosthesis users with at least 6 months of last maintenance. Exclusion criteria were: use of antibiotics in the last 3 months, diabetes, problems associated with immunosuppression, xerostomia, smokers, motor or cognitive problems, fracture or repair in the base of the prosthesis and loose teeth. The prostheses were unscrewed, washed with 0.89% sodium chloride, stained with 1% eosin y and photographed. The area covered by biofilm was delimited and quantified using the photographs obtained using the Image J software. For microbiological analysis, biofilm samples were collected from the prostheses and inserted in 0.89% sodium chloride buffered. The suspension was serially diluted to 1: 107 and seeded on chromogenic agar media to identify bacteria and fungi. The plates were incubated for 48 hours at 37 ° C for further counting of colony forming units (CFU / mL). In addition, DNA hybridization (checkerboard) was performed, employing 42 genomic DNA probes for gram-negative, gram-positive bacterial species and yeasts. Data were analyzed by the Mann-Whitney test and Spearman correlation (=0,05). There was a mean of 62% of area stained by biofilm on the gingival surface of the prostheses. Enterococcus spp (5.82 ± 1.38 log10 CFU / mL) and S. aureus (5.75 ± 2.02 log10CFU / mL) were the microorganisms with the highest count and prevalence in the culture method. Age did not influence results. Patients with 5 implants had less biofilm compared to those who had 4 implants (p = 0.031), but with a higher E. coli count (p = 0.039). In the analysis of DNA hybridization, S. pneumoniae, V. parvula, and F. nucleatum showed the highest signal intensity and were prevalent in all samples. Other microbial species were also detected. Patients older than 65 years presented a higher signal for C. tropicalis (p = 0.049). Patients with 5 implants presented reduction of signal for several species. It was concluded that biofilm was formed in total mandibular implant-supported prostheses with at least 6 months of use, and that such biofilm consists of microorganisms known to be pathogenic to the oral cavity or systemic health of more susceptible patients.